PENGARUH RASIO PELARUT TERHADAP EKSTRAKSI DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Amalia Noviyanty; Chitra Anggriani Salingkat; Syamsiar Syamsiar (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
This study aims to determine the effect of the ratio of solvents to extract yield, phenolics total and IC50 values ​​of red dragon fruit peel and also get the optimal solvent ratio to obtain extract yield, phenolics total and the highest or best IC50 values ​​of red dragon fruit peel extracts. The solvent ratio used there are 6 levels of the ratio: 2:1; 3:1; 4:1; 5:1; 6:1 and 7:1 (v/w). The data obtained were analyzed using a Completely Randomized Design that was applied to observations of extract yield, phenolics total and IC50 values, if the treatment had a very significant or significant effect followed by continued Tukey HSD test at 1% or 5% level. The results showed that the solvent ratio very significantly affected the extract yield, phenolics total and IC50 value of red dragon fruit peel extract. The solvent ratio of 4:1 (v/w) produced extract yield, phenolics total and IC50 values the highest or best i.e 26.22%, 71.56 ppm, and 124.62 ppm. Keywords : IC50, the red dragon fruit skin, solvent ratio, phenolics total